2002
DOI: 10.1074/jbc.c200150200
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Dependence of MDM2 and MDMX in Their Functional Inactivation of p53

Abstract: MDMX, an MDM2-related protein, has emerged as yet another essential negative regulator of p53 tumor suppressor, since loss of MDMX expression results in p53-dependent embryonic lethality in mice. However, it remains unknown why neither homologue can compensate for the loss of the other. In addition, results of biochemical studies have suggested that MDMX inhibits MDM2-mediated p53 degradation, thus contradicting its role as defined in gene knockout experiments. Using cells deficient in either MDM2 or MDMX, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
260
5
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(285 citation statements)
references
References 10 publications
19
260
5
1
Order By: Relevance
“…The results show that in the absence of Mdm4, the transactivation of mdm2 is stimulated, leading to increased Mdm2 protein levels. In contrast to previous transfection studies, 40 these data suggest that Mdm4 does not affect Mdm2 protein stability significantly. This was indeed directly tested and the half-life of Mdm2 was found to be similar in p53 DP/DP cells and p53 DP/DP mdm4 À/À cells, as well as in p53 LSL/-and p53 LSL/-mdm4 À/À MEFs (Toledo et al, unpublished data).…”
Section: Mdm4 Does Not Modulate P53 Levels Independently Of Mdm2contrasting
confidence: 99%
See 2 more Smart Citations
“…The results show that in the absence of Mdm4, the transactivation of mdm2 is stimulated, leading to increased Mdm2 protein levels. In contrast to previous transfection studies, 40 these data suggest that Mdm4 does not affect Mdm2 protein stability significantly. This was indeed directly tested and the half-life of Mdm2 was found to be similar in p53 DP/DP cells and p53 DP/DP mdm4 À/À cells, as well as in p53 LSL/-and p53 LSL/-mdm4 À/À MEFs (Toledo et al, unpublished data).…”
Section: Mdm4 Does Not Modulate P53 Levels Independently Of Mdm2contrasting
confidence: 99%
“…One possible scenario, based on the observation that Mdm2 and Mdm4 heterodimerize, is that the two proteins work together to inhibit p53. 39,40 However, the molecular mechanisms underlining the abilities of both Mdm proteins to regulate p53 activity have yet to be clarified in vivo. 10 Conditional alleles have now been developed that yield further insight into how and in what cell types Mdm2 and Mdm4 regulate p53 (Figure 1).…”
Section: Mdm2 and Mdm4 Are Required To Control P53 In Neuronal Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The p53 repressor MDMX is overexpressed in HTLV-1-transformed cells and in ex vivo ATL samples MDM2-related protein MDMX is a negative regulator of p53 function, which is overexpressed in a wide spectrum of human tumors that retain wild-type p53 (Gu et al, 2002). We investigated the expression levels of MDMX in both HTLV-I cell lines and ATL patients and found that, except for C10MJ, HTLV-I-transformed cells overexpressed MDMX (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%
“…It has also been suggested that MdmX may regulate the stability of p53 indirectly. Mdm2 and MdmX interact through their RING fingers and this interaction can stabilize Mdm2 and promote Mdm2-mediated degradation of p53 (Tanimura et al, 1999;Gu et al, 2002). However, in mice MdmX knockout increases p53 transcriptional activity but has little or no effect on p53 levels (Marine et al, 2006).…”
Section: Introductionmentioning
confidence: 99%